Behavioral Determinants Of Housing Consumer Purchasing Decisions In Medan City - Yahya Tanjung (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study aims to determine and analyze the influence of intrinsic and extrinsic factors on the behavior of housing purchase decisions in the city of Medan. The type of research used in this research is associative research with a quantitative approach. The population in this study is housing consumers in the city of Medan, North Sumatra whose number cannot be determined/unlimited. The sampling method used a nonprobability sampling method with a purposive sampling technique, where the researcher collects information from the most complete and fulfills various information needs. And accidental sampling provides questionnaires directly/coincidentally to meet the respondents who are said to be appropriate and worthy of the existing research. with the zikmund formula so that the number of research samples was 96 respondents. Methods of data collection is done by means of questionnaires and interviews. The data analysis method used is multiple linear regression analysis. Results Based on the research obtained partially and simultaneously, it shows that intrinsic and extrinsic factors influence purchasing decision behavior in the city of Medan. The results of the coefficient of determination test obtained the Adjusted R square value of 0.768 (76.8%). This shows that the intrinsic and extrinsic factors are able to explain the behavior of purchasing decisions by 76.8%, while the remaining 23.2% is influenced by other variables not examined in this study.